EFFECT OF DRILL AND AGILITY TRAINING ON STUDENTS' VOLLEYBALL LEARNING OUTCOMES AT SMP N2 MEDAN TP. 2023/2024: PENGARUH LATIHAN DRILL DAN KELINCAHAN TERHADAP HASIL BELAJAR BOLA VOLI SISWA DI SMP N2 MEDAN TP. 2023/2024 - Geregorian Simbolon, Andreas (UPMI Proceeding Series, 2023)
This type of research is experimental research. This research aims to prove the effect of drill and agility training on student volleyball learning outcomes at SMP N2 Medan TP. 2023/2024. The design used in this research was One Group Pretest-posttest design. The population used in this research was 30 people. The sample from the research was SMA N2 Medan. In this research, from a population of 30 players, 20 players were selected using purposive sampling. The data collection technique in this research used a volleyball playing test. The data that will be collected in this research is pre-test data on drill passing and agility training before the sample is given treatment, and post-test data after the sample is given treatment using the drill passing model. Before testing the hypothesis, it is necessary to test the prerequisites. Testing of measurement data that influences research results aims to help make analysis better. For this reason, in this research the normality and homogeneity of the data will be calculated. Based on the results of research and data analysis, it has been proven that there is an influence between Drill Training and agility and student learning outcomes at SMA N2 Medan with a calculated r of 0.3934 and an r table of 0.320, because rcount > Table (0.5578>0.320) in The significance level is 5%, so it can be said that drill and agility training on volleyball learning outcomes is valid and can be used in data collection for more details. Learning outcomes questionnaire Based on the results of the reliability test calculation of the learning outcomes questionnaire using the Alpha Cronbach formula in Microsoft Excel and SPSS 2.2, it is known that the item variance is 19.468 and the total variance is 148.2714, it is known that the reliability value is 0.915 and after consulting the correlation index it is included in the very high category. . According to (Ghazali, 2016) a Cronbach's Alpha value > 70 is declared Reliable.